2015
DOI: 10.3390/molecules20058440
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Chemical Composition and Antimicrobial Activity of Essential Oils from Brazilian Plants—Eremanthus erythropappus (Asteraceae), Plectrantuns barbatus, and P. amboinicus (Lamiaceae)

Abstract: Abstract:The chemical composition and antimicrobial activity of essential oils obtained from three Brazilian plant species-leaves and branches of Eremanthus erythropappus (Asteraceae), leaves of Plectranthus barbatus, and leaves of P. amboinicus (Lamiaceae)-were determined. Analysis by GC/MS and determination of Kovats indexes both indicated δ-elemene (leaves-42.61% and branches-23.41%) as well as (−)-α-bisabolol (leaves-24.80% and stem bark-66.16%) as major constituents of E. erythropappus essential oils. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
2
17
1
2
Order By: Relevance
“…In the study, all Gram-positive bacteria were effectively inhibited with an MIC of 512  μ g/mL. The bacterial strain S. epidermidis was inhibited by the essential oils of Plectranthus barbatus and P. amboinicus with an MIC value of 31  μ g/mL [4, 33]. Likewise, the essential oil of Plectranthus neochilus was shown to inhibit some cariogenic bacteria such as E. faecalis, S. salivarius, Streptococcus sobrinus, Streptococcus sanguinis, S. mitis, S. mutans, and Lactobacillus casei [59].…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, all Gram-positive bacteria were effectively inhibited with an MIC of 512  μ g/mL. The bacterial strain S. epidermidis was inhibited by the essential oils of Plectranthus barbatus and P. amboinicus with an MIC value of 31  μ g/mL [4, 33]. Likewise, the essential oil of Plectranthus neochilus was shown to inhibit some cariogenic bacteria such as E. faecalis, S. salivarius, Streptococcus sobrinus, Streptococcus sanguinis, S. mitis, S. mutans, and Lactobacillus casei [59].…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
“…Similarly, the inhibitory potential of Aegle marmelos oil against C. albicans, A. niger, and F. oxysporum was demonstrated. The essential oils extracted from Eremanthus erythropappus , P. barbatus, and P. amboinicus were shown to inhibit the growth of C. albicans, Cryptococcus gattii, Cryptococcus neoformans, and S. cerevisiae [33]. Papajani et al [88] have reported the antifungal activity of rosemary essential oil against dermatophytes such as A. cajetani , E. floccosum , M. gypseum , M. canis , T. violaceum , T. mentagrophytes , T. rubrum , and T. tonsurans and phytopathogens such as Botrytis cinerea and Pleomorphomonas oryzae .…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
“…In Brazil, the main constituents of Plectranthus amboinicus essential oil were carvacrol and thymol . In another study in Brazil, p ‐cymene (12.01%), γ ‐terpinene (14.74%), carvacrol (37.70%), and ( Z )‐caryophyllene (14.07%) were reported to be the major constituents . In Malaysia, the main components of the oil of Plectranthus amboinicus were 3‐carene (20.78%), α ‐terpinene (6.04%), o ‐cymene (5.06%) γ ‐terpinene (8.94%), camphor (17.96%), and carvacrol (19.29%) .…”
Section: Resultsmentioning
confidence: 99%
“…[39] In another study in Brazil, p-cymene (12.01%), c-terpinene (14.74%), carvacrol (37.70%), and (Z)-caryophyllene (14.07%) were reported to be the major constituents. [40] In Malaysia, the main components of the oil of Plectranthus amboinicus were 3-carene (20.78%), a-terpinene (6.04%), o-cymene (5.06%) c-terpinene (8.94%), camphor (17.96%), and carvacrol (19.29%). [41] In Morocco, carvacrol (23.0%), camphor (22.2%), d-3-carene (15.0%), c-terpinene (8.4%), and o-cymene (7.7%) were the major constituents of the oil.…”
Section: Gc/ms Analysis Resultsmentioning
confidence: 99%
“…and Cryptococcus spp. -, besides antinociceptive, anti-inflammatory, schistosomicidal, antiedematogenic and antiulcerogenic ones (Hillen et al, 2012;Nascimento et al, 2007;Silvério et al, 2013;Santos et al, 2015;Sousa et al, 2008a;Almeida et al, 2012;Keles et al, 2010). However, anticaries, antimycobacterial and antileishmanial activities of EOs from E. erythropappus have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%